Neuropathic Pain and its Management - Bag, Anupam Kanti; R Hiremath, Shobha Rani (Indian Journal of Pharmacy Practice)
Pain is a distressing sensory and emotional experience connected to real or potential tissue damage, or one that is portrayed as such damage, according to the International Association for the Study of Pain (IASP). There are many different pathophysiologic processes and interpretations of pain, which can vary greatly in severity, quality, and duration. The process that follows an initial injury or illness of the somatosensory nerve system is known as neuropathic pain. Hyperalgesia, an abnormal heightened sensitivity to stimuli, and allodynia, a nociceptive reaction to non-noxious stimuli are characteristics of neuropathic pain. The aetiology or anatomic location of this illness, which is the outcome of numerous different pathogenic pathways, is typically used to define it.